Optimalisasi Penggunaan Anggaran dalam Menunjang Proses Tri Darma Pendidikan pada Perguruan Tinggi - Ewif Frinosta (SAFE-Network, 2021)
Higher education has an obligation to carry out education, research, and community service based on the tridarma of higher education. Adi Karya Technical Academy (ATAK) is one of the private universities in Kerinci Regency, and also has a vision and mission that is in line with tridharma. To support the tridharma process of education in ATAK, it use of the budget needs to be optimized. Optimize the use of the budget, one processes that possible to do predictions budget's utilization. The data processed is the use of the 2017, 2018 and 2019 budgets at ATAK Universities. The result predections use budget's get it from simulation process the monte carlo are 89.79% for predictions in 2018, 84.73% for predictions for 2019 and 85.52% for 2020. In this case the monte carlo that possible apply to do predictions budget's utilization the following year.